2016
DOI: 10.1080/10400435.2016.1171807
|View full text |Cite
|
Sign up to set email alerts
|

Service innovation through social robot engagement to improve dementia care quality

Abstract: Assistive technologies, such as robots, have proven to be useful in a social context and to improve the quality of life for people with dementia (PwD). This study aims to show how the engagement between two social robots and PwD in Australian residential care facilities can improve care quality. An observational method is adopted in the research methodology to discover behavioural patterns during interactions between the robots and PwD. This observational study has undertaken to explore the improvement arising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(116 citation statements)
references
References 42 publications
4
109
0
3
Order By: Relevance
“…Past research has demonstrated social robots' capabilities to further psychological well-being in vulnerable populations. Social robots are not only capable of evoking empathy, they can decrease loneliness in the elderly, improve social capabilities of older people with dementia, elicit novel social behavior from people with autism, and foster social engagement and self-disclosure among adolescents (Chu et al, 2017; Kwak et al, 2013;Martelaro et al, 2016; Robinson et al, 2013;Rose & Björling, 2017;Scassellati et al, 2012). While studies have shown that sharing stressful experiences can help reduce stress, few studies have delved into the design of a stress-sharing interaction between a human and a robot (Hofmann et al, 2012; J. H. Kahn, Achter, & Shambaugh, 2001; J. H. Kahn & Hessling, 2001;Zhang, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Past research has demonstrated social robots' capabilities to further psychological well-being in vulnerable populations. Social robots are not only capable of evoking empathy, they can decrease loneliness in the elderly, improve social capabilities of older people with dementia, elicit novel social behavior from people with autism, and foster social engagement and self-disclosure among adolescents (Chu et al, 2017; Kwak et al, 2013;Martelaro et al, 2016; Robinson et al, 2013;Rose & Björling, 2017;Scassellati et al, 2012). While studies have shown that sharing stressful experiences can help reduce stress, few studies have delved into the design of a stress-sharing interaction between a human and a robot (Hofmann et al, 2012; J. H. Kahn, Achter, & Shambaugh, 2001; J. H. Kahn & Hessling, 2001;Zhang, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Aside from individual interaction, the robots also engaged in singing, and other activities with patients. The authors reported that the subjects responded positively to the two robots, and patient engagement with the robots improved significantly over the course of the multi-year study [35]. Other models will be discussed in the following sections.…”
Section: Efficacy Of Sarsmentioning
confidence: 99%
“…Some functions, such as inputting the user's name, were too difficult for patients to handle; the height and slant of the screen also made it difficult for patients to manipulate [3]. More complicated social robots that use voice recognition and, in some cases, facial expressions and body language to communicate are generally well-received by subjects and caregivers [35,45]. In the aforementioned Spain-Poland survey, users, caregivers, and medical staff greatly preferred voice-based communication to other options, and voice communication is the most natural and simple way of interaction for most patients.…”
Section: Acceptance Needs and Preferencesmentioning
confidence: 99%
“…Some new assistive technologies are potentially valuable for improving the health and care of people living with dementia: memory and communication aids, safety devices, 8 global positioning system (GPS) tracking, 9 11 companion robots 12 14 and technology for so-called smart homes 15 , 16 . Indeed, it has been argued that these technologies may have a triple-win effect because they may: (i) delay entry into institutional care; (ii) reduce the burden on caregivers; and (iii) improve the quality of life of dementia patients 17 .…”
Section: Assistive Technologiesmentioning
confidence: 99%